Outer membrane protein OMP76 of Riemerella anatipestifer contributes to complement evasion and virulence by binding to duck complement factor vitronectin - Sen Li; Yanhua Wang; Rongkun Yang; Xiaotong Zhu; Hongying Bai; Xiaojian Deng; Jiao Bai; Yang Zhang; Yuncai Xiao; Zili Li; Zhengfei Liu; Zutao Zhou (Virulence)
Riemerella anatipestifer is an important bacterial pathogen in poultry. Pathogenic bacteria recruit host complement factors to resist the bactericidal effect of serum complement. Vitronectin (Vn) is a complementary regulatory protein that inhibits the formation of the membrane attack complex (MAC). Microbes use outer membrane proteins (OMPs) to hijack Vn for complement evasion. However, the mechanism by which R. anatipestifer achieves evasion is unclear. This study aimed to characterise OMPs of R. anatipestifer which interact with duck Vn (dVn) during complement evasion. Far-western assays and comparison of wild-type and mutant strains that were treated with dVn and duck serum demonstrated particularly strong binding of OMP76 to dVn. These data were confirmed with Escherichia coli strains expressing and not expressing OMP76. Combining tertiary structure analysis and homology modelling, truncated and knocked-out fragments of OMP76 showed that a cluster of critical amino acids in an extracellular loop of OMP76 mediate the interaction with dVn. Moreover, binding of dVn to R. anatipestifer inhibited MAC deposition on the bacterial surface thereby enhancing survival in duck serum. Virulence of the mutant strain ΔOMP76 was attenuated significantly relative to the wild-type strain. Furthermore, adhesion and invasion abilities of ΔOMP76 decreased, and histopathological changes showed that ΔOMP76 was less virulent in ducklings. Thus, OMP76 is a key virulence factor of R. anatipestifer. The identification of OMP76-mediated evasion of complement by recruitment of dVn contributes significantly to the understanding of the molecular mechanism by which R. anatipestifer escapes host innate immunity and provides a new target for the development of subunit vaccines.